'La Main négative': Limit-Case and Primal Scene of Art. Issue 3 (November 2021) - Malt, Johanna
Abstract : Negative handprints or hand-stencils, which occur in many prehistoric sites around the world, occupy a particular place in accounts of rock art. Although they frequently occur alongside paintings, their indexical status as imprints leads them to be treated separately from other types of representations that are more easily accepted as such. This article argues that the negative handprint operates as a kind of limit-case for definitions of art. I examine how it has given rise to imagined scenarios of making — what we might call primal scenes of art — by writers including Georges Bataille, Maurice Blanchot and Marguerite Duras. While its logic of presence invites us to think about it as a point of origin, a trace that connects us to our earliest human ancestors, I show how it can be read against that logic of presence through the lens of one particular 'primal scene', that imagined by Jean-Luc Nancy. In this reading, it is precisely the question of absence or distance that gives the handprint its status as a point of origin that undoes the very idea of origins.